Effects of a Complex Intervention Exercise Program on Lumbar Extension Strength and Stability in Female Patients with Lower Back Pain - Soonyoung KIM; Kyoungkyu JEON (Tehran University of Medical Sciences, 2017)
Effects of a Complex Intervention Exercise Program on Lumbar Extension Strength and Stability in Female Patients with Lower Back Pain